PENYULUHAN TENTANG STUNTING DI DESA BANGSRI KECAMATAN JEPON KABUPATEN BLORA - Dyan Maryana; Maria Wiwik Setyaningsih (Bajang Institute, 2023)
Stunting is a serious nutritional problem for children in Indonesia. Currently the stunting rate in Indonesia is at 37.2% or the equivalent of 8 million children with suboptimal growth. Based on data from the Jepon Health Center, several health problems exist in Bangsri Village, Jepon sub-district, Blora Regency, one of which is stunting of 21.5%. The causes of stunting are based on influencing factors, namely exclusive breastfeeding, nutritional knowledge of mothers under five and education level of mothers under five. The purpose of this activity is to find out nutritional problems and be able to provide nutrition interventions that are appropriate to the nutritional problems that exist in Bangsri Village, Jepon sub-district, Blora Regency. The method used is the lecture method. The results show an increase in the knowledge of mothers who have toddlers.